Kriteria Utama dalam Pembangunan Laman Web Berkaitan Hadith: Satu Analisis dan Cadangan: The Main Criteria in Hadith Website Development: Analysis and Recommendations - Ahmad, Khadher; Suliaman, Ishak; Ahmad Shah, Faisal; Mohd Rokhibi, Ibrahim Adham (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
Nowadays, referring to the sources from the internet through websites, apps and private blogs has become a trend among the public. In fact, some of these internet resources do not have any authority and proper control so that it is possible anything can be referred and followed without restrictions and boundaries. Looking at the field of hadith, it is undeniable that websites became a source for the hadith reference. However, the authority and quality of some sites are dissatisfied because they do not meet the minimum criteria as a source of hadith. This article aims to explain the criteria required for using websites as sources of hadith. Through the inductive and deductive analysis methods, this study found ten important criteria for development of hadith websites; [1] Providing full text of hadith; [2] Using scholarly translation; [3] Providing information of the source and takhrij al-hadith (retrieval of hadith); [4] Supplying a brief meaning of the hadiths; [5] A group of qualified committee members or oganizations; [6] Furnishing with friendly interface; [7] Attaching shajarah al-asānid (chain of transmissions ‘tree’); [8] Implementing the themes of the hadith; [9] Categorization of hadiths based on the title of the book; [10] Providing different hadiths as an alternative of fabricated or weak hadiths. This research concludes that these criteria are importance for the development of hadith websites in order to maintain and preserve the authority of the hadith as a referential source of community today.